Climate, food (in)security and conflict in the Bangladesh delta: Myths and puzzles - Suza, Ma; Warner, Jeroen; van Dijk, Han (SAGE Publications, 2024)
Bangladesh is customarily presented as a poster child for climate change and conflict given its dense population and susceptibility to climate variability. This vulnerability exacerbates existing challenges such as food insecurity and conflict potential. Crises like pandemics and conflicts are external drivers stressing already compromised domestic governance, such as violent politics, poor rule of law, and corruption, further compounding the challenges of land and water resource management and affecting food (in)security in Bangladesh. While we will argue that Bangladesh’s all-out (‘securitised’) efforts to achieve food security are largely successful and there is no evidence of climate conflict related to food, this does not obviate very real food security challenges in remote areas. However, these have not built up to the sense of frustration associated with food riots or community violence. Navigating the possible linkages between climate, food (in)security, and conflict requires debunking common myths and identifying unresolved research puzzles in Bangladesh’s context. These myths promote the oversimplification of complex issues and may lead to misinformed policies and actions. Future research needs to be focused on understanding how climate factors interact with local economic, political, and social dynamics, including governance mechanisms, religious and ethnic tensions, economic inequality, grievances, and political exclusion.